Investigating the relationship between physical cognitive tasks and a social cognitive task in a wild bird - Grace Blackburn; Benjamin J. Ashton; Alex Thornton; Holly Hunter; Sarah Woodiss-Field; Amanda R. Ridley (Animal Cognition)
Abstract Despite considerable research into the structure of cognition in non-human animal species, there is still much debate as to whether animal cognition is organised as a series of discrete domains or an overarching general cognitive factor. In humans, the existence of general intelligence is widely accepted, but less work has been undertaken in animal psychometrics to address this question. The relatively few studies on non-primate animal species that do investigate the structure of cognition rarely include tasks assessing social cognition and focus instead on physical cognitive tasks. In this study, we tested 36 wild Western Australian magpies (Gymnorhina tibicen dorsalis) on a battery of three physical (associative learning, spatial memory, and numerical assessment) and one social (observational spatial memory) cognitive task, to investigate if cognition in this species fits a general cognitive factor model, or instead one of separate physical and social cognitive domains. A principal component analysis (PCA) identified two principal components with eigenvalues exceeding 1; a first component onto which all three physical tasks loaded strongly and positively, and a second component onto which only the social task (observational spatial memory) loaded strongly and positively. These findings provide tentative evidence for separate physical and social cognitive domains in this species, and highlight the importance of including tasks assessing both social and physical cognition in cognitive test batteries.